Analisa Kelayakan Usaha Konveksi Kaos (T-Shirt) Dengan Menggunakan Metode SWOT Di UMKM Kabupaten Sidoarjo Kecamatan Taman, Menanggal - Habrila, Nizar; M. Nushron Ali Mukhtar (International Journal of Economics, Business and Accounting Research (IJEBAR), 2025)
The fashion shopping trend in Indonesia has increased during the COVID-19 pandemic. This has led many business owners to capitalize on online business opportunities, transforming them into a trend in the current business world. This study describes how to analyze business feasibility using the SWOT method and the factors that influence business feasibility based on SWOT. A SWOT analysis includes an internal environmental analysis, namely strengths and weaknesses, as well as an external environmental analysis, namely opportunities and threats. To overcome these difficulties, the data analysis techniques used in this study were SWOT analysis, the IFAS Matrix, the EFAS Matrix, and the SWOT Matrix. This study used primary data, through observation and interviews. The results of the study showed that strengths include good quality, affordable prices, excellent service, strategic location and environment, and product variety. The strength matrix calculation results in a value of 3.8. Weaknesses obtained a value of 3.58. Opportunities obtained a value of 3.04. The Threats score was 2.94. Therefore, the overall strategy can be identified by maximizing opportunities, minimizing weaknesses, using strengths as a fundamental element in business planning, and suppressing existing threats to the t-shirt convection company for the company's future sustainability.